The soil seed bank in abandoned tropical pastures: source of regeneration or invasion? - Leonel López-Toledo; Miguel Martínez-Ramos (Revista Mexicana de Biodiversidad)
We assessed the availability of both pioneer and non-native species in the soil seed bank of old-growth forest and recently abandoned pasture, to evaluate whether the soil seed bank in these pastures represents a source of regeneration of species from adjacent old-growth forest or of invasion by non-native species. Our study was conducted at Selva Lacandona, Chiapas, Mexico. Soil samples were randomly collected from 6 sites in old-growth forest, and 6 sites in abandoned pastures. Seedlings from soil samples were identified and classified into pioneer, non-native (weeds/ graminoids), and other forest species. Pioneer species seeds were virtually absent in pastures, but represented ~30% of seeds in the forest. Non-native species comprised ~99% of the soil seed bank in pastures. In the forest, soil seed bank density of weeds and graminoids decreased with increasing distance (up to 4 km) from agricultural fields, and comprised up to 25% (Mean ± 1SE= 16 ± 7) of the seed bank. Our results show a near total elimination of pioneer species from the soil seed bank in pastures, and considerable invasion of the borders of the Montes Azules reserve by seeds of non-native species. Thus, in the region studied, the soil seed bank in abandoned pastures represents a source of invasion by non-native species into old-growth forest rather than a potential source of forest regeneration.